PENYELENGGARAAN BANTUAN HUKUM BAGI MASYARAKAT TIDAK MAMPU DI KABUPATEN SOPPENG - Fitrah, A. Nurhafidhah; Sultan, Lomba; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
Legal aid is a constitutional right of every citizen to guaranteed legal protection and guaranteed equality before the law. This study aims to find out how the application of local regulations regarding the provision of legal aid to the poor in Soppeng Regency. This research is a qualitative field research, with a normative juridical approach. The results of the research show that the provision of legal aid for the poor through Regional Regulation No. 1 of 2017 is a manifestation of the commitment of the local government of Soppeng Regency to providing protection, guarantees of human rights, and access to justice for underprivileged people in the justice system. In addition, legal aid for People Cannot Afford It the answer to equality before the law which needs to be regulated in laws and derivative regulations. With the existence of legal aid regulations, equality before the law and access to justice for the community can be realized.